A Study on the Influence of Multi-Teaching Strategy Intervention Program on College Students’ Absorptive Capacity and Employability - Peng, Michael Yao-Ping; Wang, Lin; Yue, Xiaoyao; Xu, Yan; Feng, Yongjun (Frontiers in Psychology, 2021)
Student employability is also the key-point which needs to be improved by higher education institutions. Whether high student learning outcome can represent high employability is still a problem needs to be figured out. Furthermore, students with high employability can find good jobs after graduation and have good performance in the workplace, and this has always been attributed to the success of university education, and thus brings university a good reputation. Therefore, this study intends to explore the cultivation and improvement of employability, and teachers’ teaching level and students’ learning ability are added to learn about how these variables affect students’ employability. In this study, 442 copies of questionnaire were collected to investigate the relation among pedagogy for employability, problem-based learning, absorptive capacity and student employability based on structural model. The SEM results show that pedagogy for employability and problem-based learning positively correlate to absorptive capacity; pedagogy for employability and absorptive capacity positively correlate to student employability. Then 221 students from the school of management were taken as the objects to analyze case teaching strategy intervention and discuss the differential results of all variables. The results have shown that the test group is superior to the control group in each variable performance, so that the intervention strategy is proved effective. Based on these findings, the researchers proposed feasible suggestions for related issues and future research.